Hubungan Faktor Maternal dan Postnatal dengan Kejadian Stunting pada Balita - Gracelia Mona Lorenza; Atik Ba’diah; Ira Jayanti (Window of Midwifery Journal, 2026)
Stunting remains an important public health concern in Indonesia. In North Bengkulu, the prevalence increased from 20.7% in 2021 to 22.8% in 2022. Maternal conditions during pregnancy and postnatal characteristics are assumed to contribute to stunting among toddlers. This study examined the association between maternal and postnatal factors and stunting among toddlers in the working area of Lubuk Durian Community Health Center, North Bengkulu. A quantitative cross-sectional design was applied. The sample included 209 children aged 3-5 years, selected using purposive sampling. Data were obtained through interviews, anthropometric measurements, and a review of maternal and child health books. The data were analyzed using chi-square tests and multiple logistic regression. The prevalence of stunting was 37.8%. Bivariate analysis demonstrated significant associations between a history of chronic energy deficiency (p=0,000), maternal anemia (p=0,000), low birth weight (p=0,000), and short birth length (p=0,000) and stunting. Multivariate analysis identified a history of chronic energy deficiency as the strongest factor (OR=11,81; 95%CI=4,61-30,22). Maternal factors, namely chronic energy deficiency and anemia, as well as postnatal factors, including low birth weight and short birth length, were associated with stunting, with chronic energy deficiency being the most dominant determinant. Strengthening nutritional programs for pregnant women, early nutritional screening, and continuous nutrition education are required to prevent stunting